Exploring the Philosophy of Life: Study of Muhammad Abed Al-Jabiri's Thought in the Context of Modernity and Tradition - Qosim, Nanang; Amin, Nasihun (International Journal of Islamic Studies Issues, 2025)
This research aims to explore the philosophy of Muhammad Abed al-Jabiri's life, especially regarding the interaction between tradition and modernity in the context of the Islamic world. Al-Jabiri proposes a critical approach to Islamic intellectual heritage through epistemological analysis that divides tradition into three main systems: bayani (textualism), irfani (mysticism), and burhani (rationalism). He identified the dominance of bayani and irfani as an obstacle to the advancement of Islamic thought, and encouraged the rise of burhani to strengthen rationality and scientific methods in interpreting traditions. According to al-Jabiri, modernity is not something that should be rejected or accepted without consideration, but must be combined with Islamic values that have been reformed. With this approach, al-Jabiri proposed a reinterpretation of tradition that not only preserved the essence of Islamic culture, but also opened up opportunities for social and intellectual transformation. His thinking offers solutions to the challenges of globalization, intellectual stagnation, and the dynamics of modernity, with an emphasis on the importance of dialogue between tradition and modernity. The study concludes that al-Jabiri's thought has great relevance in building an intellectual framework that can bridge Islamic cultural identity with the demands of the times, thus allowing Muslim societies to play an active role in the ever-changing global world